ANALISIS EMPIRIS TATA KELOLA FASILITAS PERBATASAN BERBASIS CONNECTIVITY AND COMMON PROSPERITY GUNA MENCEGAH PERILAKU KORUPSI - Pratama, Yogi; Darajati, Muhammad Rafi (Lembaga Penelitian dan Pengabdian kepada Masyarakat STIH Awang Long, 2024)
This research aims to analyze the governance of border facilities at Entikong Border Post to prevent corrupt practices, particularly in the management of low-cost apartments. A qualitative case study approach was employed to investigate the operational frameworks and decision-making processes. Data was collected through interviews, document analysis, and observation. The findings reveal that transparent and collaborative governance practices can significantly reduce corruption risks. This research underscores the importance of connectivity-driven governance strategies to promote sustainable development and common prosperity in border regions.